Cohesive zone modeling of the buckling behavior of a fusion-joined, additive-manufactured wind blade - Dongyang Cao; Hongbing Lu; Daniel Todd Griffith (Academia Materials Science)
In this article, the use of additive-manufactured thermoplastics, specifically polylactic acid (PLA), to fabricate segments of wind turbine blades with core sandwich composites was verified through their compressive bucking performance, demonstrating their cost-effectiveness in manufacturing and transportation. A small wind blade was constructed by joining these segments to demonstrate their application potential in renewable energy technologies. The study’s focus was on the compressive buckling behavior of these fusion-joined blades, particularly on the heterogeneity at the resistance welding bond line. An approach was adopted to integrate a hybrid of solid and cohesive elements within the cohesive zone modeling (CZM) framework using the Abaqus–Riks method. This allowed us to insert a thin layer of solid–cohesive elements at the bond line, enhancing the fidelity of our simulations. The validity of our numerical results was examined by comparing them with the surface strain field measured by digital image correlation (DIC) and assessing the compressive response. Furthermore, the applicability of classical Euler and Johnson formulas was evaluated in predicting buckling loads and modes. The Euler formula was found adequate for the first flexural buckling mode in beams with high slenderness ratios (≥12). Our findings demonstrate that the hybrid CZM approach effectively models the buckling behavior of fusion-joined beams, accommodating a range of slenderness ratios (6 to 18) and various buckling modes. This study provides insights into the structural analysis of fusion-joined components for potential applications of additive manufacturing in wind energy.